Autonomic activity and leptin in Africans and whites: the SABPA study - Pieterse, Chiné; Schutte, Ramoteme, L.; Schutte, Aletta E. (Wolters Kluwer/Lippincott, Williams & Wilkins, 2014)
Objectives: Evidence exists that leptin enhances sympathetic activity and may thereby contribute to the development of obesity-related hypertension. Sympathetic activation also seems more prominent in Africans than whites. We compared leptin levels, and different markers of autonomic activity between Africans and whites, and determined whether a relationship exists between leptin and autonomic activity. Methods: The study included 409 African and white school teachers (aged, 44.6 ± 9.6 years). We determined leptin in serum and measured ambulatory blood pressure. Markers reflecting autonomic activity included renin, cortisol, baroreflex sensitivity, ambulatory heart rate and heart rate variability (HRV) components (assessed by 24-h ECG recordings in the frequency and geometric domain). Results: Africans had higher leptin levels, BMI, blood pressure and heart rate (all P < 0.001) as well as lower HRV triangular index and HRV total power (P < 0.001). After also adjusting for BMI in multivariate regression analyses, in African men, renin ([beta] = 0.228; P = 0.033), night-time heart rate ([beta] = 0.184; P = 0.034), HRV triangular index ([beta] = -0.230; P = 0.010) and HRV total power ([beta] = -0.214; P = 0.046) associated with leptin. In white men, leptin associated with 24-h heart rate ([beta] = 0.376; P < 0.001), as well as day and night-time heart rate (both P < 0.01), HRV triangular index ([beta] = -0.335; P < 0.001) and HRV total power ([beta] = -0.403; P < 0.001). In African women, we observed an association of leptin with the total power component of HRV ([beta] = -0.221; P = 0.015) and a borderline association with renin ([beta] = 0.219; P = 0.057). No significant associations were apparent in the white women. Conclusion: We found that leptin is independently associated with different markers of autonomic activity, especially in men.
Keywords: autonomic nervous system; ethnicity and leptin; hypertension; sympathetic activity